Dr. Alberto Calvo — Deep Plane Facelift — Lima - Calvo, Alberto (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Alberto Calvo, practicing in Lima, Peru. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003343; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; peru; lima